MADRASAH HIJAU/GREEN SCHOOL DALAM PENINGKATAN KESADARAN LINGKUNGAN HIDUP BERBASIS MADRASAH INSPIRATIF DI MTsN 1 JOMBANG - 'Azah, Nur (Al Tadib : Jurnal Ilmu Pendidikan, 2021)
Environmental awareness is a concept of environmental protection and management. There is a mutualism symbiosis between human behavior and natural conditions by itself as caliph fi al ardh. The research objective is to find a model of green school program policy, an environment-based curriculum, participatory-based activities, and supporting infrastructure for inspiring madrasa-based learning. Descriptive research, natural background data, direct data sources from the head of the madrasa, waka curriculum, green school builder, BK, homeroom teacher, madrasa canteen, and parents. Collecting data from photo documents, activity journals, green school administration. Data validity with confirmation of research results by using triangulation as a check of the validity of research findings. The results of the research contribute to madrasa-based school development institutions that inspire to strengthen knowledge, skills, manage and grow the value of environmental awareness.